2013
DOI: 10.1542/peds.2012-1126
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Type b in an Immunocompetent, Fully Vaccinated ALL Survivor

Abstract: A 7-year-old boy with a history of recurrent acute lymphoblastic leukemia (ALL), in remission, presented to primary care clinic after 2 days of progressive right hip pain with weight-bearing activities. He was otherwise asymptomatic at the time of presentation. Blood cultures revealed Gram-negative diplococci, which prompted an MRI that was significant for a hip joint effusion and femoral head bone marrow edema. The patient had no sick contacts and no significant past medical history other than ALL. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…There is limited experience on the use of vaccinations for Pneumococcus, Haemophilus, and Meningococcus [5561]; in one case, a failure is reported [62]. Effective prevention remains based on prompt antibiotic treatment of febrile at-risk patients and isolation measures to prevent contact especially during periods of severe neutropenia.…”
Section: Resultsmentioning
confidence: 99%
“…There is limited experience on the use of vaccinations for Pneumococcus, Haemophilus, and Meningococcus [5561]; in one case, a failure is reported [62]. Effective prevention remains based on prompt antibiotic treatment of febrile at-risk patients and isolation measures to prevent contact especially during periods of severe neutropenia.…”
Section: Resultsmentioning
confidence: 99%
“…One patient died of pneumococcal sepsis. Nevin et al ( 2013 ) recently reported a case of invasive H. infl uenzae in a 7-year-old who was fully immunized prior to ALL therapy but received no additional vaccine doses after chemotherapy completion. Siber ( 1980 ) looked at the incidence of infection with S. pneumoniae and H. infl uenzae from 1968 to 1977 and found that the majority of episodes of infection occurred during therapy although a small fraction also occurred after therapy completion.…”
Section: Defi Ning the Risk From Vaccine-preventable Diseasesmentioning
confidence: 99%